An Implementation of Interactive Application for the Synthesis of Communication Systems with Antenna Arrays - S. V. Kuzmin; K. O. Korovin; T. R. Raimzhanov (Известия высших учебных заведений России: Радиоэлектроника, 2020)
Introduction. Modern radar and communications systems contain phased array antennas. One of the synthesis problems of such systems is the formulation of requirements for components, modules and units which are comprised in it. To solve this problem, one needs to build a coverage area and to analyze an impact of characteristics of its parts. The quality of analysis and synthesis of such complex systems can be enhanced by use of interactive data visualization, which requires a fairly quick calculation of characteristics.Aim. Development of an interactive application for increasing the synthesis capabilities of communication systems containing antenna arrays and for improving the characteristics of systems of interest.Materials and methods. To accelerate the calculation of radiation patterns, the antenna array pattern in a form suitable for the fast Fourier transform algorithm was used. To find the required amplitude-phase distributions, Kotelnikov series expansion and genetic algorithm were used.Results. In the developed application, amplitude-phase distribution, directivity pattern of a linear equidistant array and coverage area were displayed. An interactive change of the amplitude-phase distribution at radiation elements and synthesized radiation patterns in given directions were possible. With introduction of changes to the radiation pattern, the amplitude-phase distribution and the array radiation pattern itself changed in directions other than the specified one. The coverage area was rebuilt when any of the characteristics changes. If necessary, the coverage area display could be turned off. The paper provides an example of using the application in the synthesis of a communication system with an aircraft.Conclusion. The use of the developed application allows one to extend the capabilities and significantly reduce the analysis and synthesis time of the communication secondary radar systems with antenna arrays too. Besides, the application is used for training specialists for industry enterprises.